Bangladeshi Engineering EFL Learnersa Attitudes towards Learning English: A Comparison between Public University and Private University Students. (Global Journal of Human-Social Science, 2015)
The objective of this paper is to explore Bangladeshi engineering EFL learners' attitude towards learning English. The study was conducted among 67 students of Computer Science and Engineering departments of United International University, a private University in Bangladeshi and Jahangir Nagar University, a public university in Bangladesh. Data were collected through a 34 items attitude test questionnaire. The findings report that, engineering EFL learners both in public and private universities have moderately positive emotional and cognitive attitudes and highly positive behavioral attitudes to learning English. The study also exposes that, public university students are less competent, more exam-oriented, and more discouraged by bad results. They are also more eager to continue English courses than private university learners. The study also offers some possible solutions to change the overall negative attitudes and to help public university learners stand up equally on the platform of learning the global language.
Keywords: attitude; tertiary level; english language learning